The in-situ XAS study on the formation of Pd nanoparticles via thermal decomposition of palladium (II) acetate in hydroxyl functionalized ionic liquids. (25th January 2021) - Yao, Siyu; Sun, Haolin; Ma, Ding
Abstract: The formation of palladium nanoparticles (NPs) via thermal decomposition of palladium (II) acetate in hydroxyl functionalized ionic liquid (IL) [C2 OHmim] + [NTf2 ] − was studied using in-situ energy dispersive x-ray absorption fine structure spectroscopy (DXAFS) and complementary methods such as transmission electron microscopy (TEM) and inductively coupled plasma mass spectrometry. Detailed XAFS spectra analysis unraveled that the palladium acetate trimer precursor underwent dissociation after being dispersed in ILs, which accelerated the thermal decomposition compared with other organic solvents. Based on the reaction kinetics, extened x-ray absorption fine structure spectroscopy fitting and TEM characterization results, the thermal decomposition process can be divided three successive stages namely the explosive nucleation, autocatalytic surface growth and NP attachment growth.